Quantifying the Size and Duration of a Microburst‐Producing Chorus Region on 5 December 2017. Issue 15 (15th August 2022) - Elliott, S. S.; Breneman, A. W.; Colpitts, C.; Pettit, J. M.; Cattell, C. A.; Halford, A. J.; Shumko, M.; Sample, J.; Johnson, A. T.; Miyoshi, Y.; Kasahara, Y.; Cully, C. M.; et al.
Abstract: Microbursts are impulsive (<1 s) injections of electrons into the atmosphere, thought to be caused by nonlinear scattering by chorus waves. Although attempts have been made to quantify their contribution to outer belt electron loss, the uncertainty in the overall size and duration of the microburst region is typically large, so that their contribution to outer belt loss is uncertain. We combine datasets that measure chorus waves (Van Allen Probes [RBSP], Arase, ground‐based VLF stations) and microburst (>30 keV) precipitation (FIREBIRD II and AC6 CubeSats, POES) to determine the size of the microburst‐producing chorus source region beginning on 5 December 2017. We estimate that the long‐lasting (∼30 hr) microburst‐producing chorus region extends from 4 to 8 Δ Δ MLT and 2–5 Δ Δ L. We conclude that microbursts likely represent a major loss source of outer radiation belt electrons for this event. Plain Language Summary: Microbursts are short‐duration (<1 s) bursts of electrons that precipitate from the magnetosphere into the atmosphere. Microbursts are thought to be a result of scattering by a plasma wave called chorus. Attempts have been made to understand the contribution microburst precipitation has on electron loss, which helps the outer radiation belt recover after enhancements during storms. The contribution depends on the overall size and duration of the microburst region. We combine datasets that measure chorus waves and microburst precipitation to determine the size and duration of a microburst region beginning on 5 December 2017. Our results show that microbursts are likely a significant source of electron loss. Key Points: We use multipoint observations to estimate the size of a long‐lasting microburst‐producing chorus region beginning on 5 December 2017 We estimate that the microburst‐producing chorus region for this event extends from 4 to 8 Δ Δ MLT and 2–5 Δ Δ L Microburst precipitation from this event likely constitutes a major source of electron loss from the outer radiation belt